Correlation of Gandhi with cleanliness drive and Swachh Bharat Mission: Study on methodology of spreading awareness and motivating rural section of Chandigarh to maintain hygienic conditions - Renu Gandhi (Technium Social Sciences Journal, 2020)
The cleanliness drive most popularly known as “Swacch Bharat Mission” started by Prime Minister Narendra Modi from 2nd October, 2014 to 2nd October, 2019 as a tribute to Mahatma Gandhi on his 150th Anniversary lays its foundation from Gandhi’s effort to eradicate the Untouchability and humiliation of Indians on account of their unhygienic lifestyle and poor sanitation habits. Receiving a negative feedback from white Europeans about Indians lifestyle, he observed, analyzed and accepted the views received by European’s, instead of defending them. Mahatma Gandhi motivated Indians to self-groom themselves to become capable to compete with white European’s, instead of fighting for Independence. Modi took over the drive in order to complete the incomplete task planned and furnished by Mahatma Gandhi. This drive is supported not only by each Indian citizen, but also by each educational institute, academic institutes, research institutes and many more. As a part of this program we also conducted a cleanliness drive in Daddu Majra colony, Chandigarh. The program begun while delivering talks to group of people of the colony highlighting the significance of cleanliness in day-today life of an individual as well as community. The role of community and collective effort of people in maintaining clean environment while practicing appropriate sanitation and hygienic conditions was discussed. The community was well motivated and inspired to work collectively for up liftment of their village area while maintaining proper surroundings, cleaning them regularly to prevent themselves from harmful diseases such as malaria and dengue. A special session was also conducted for Women in order to guide them to ensure proper disposal of their wastes during menstrual cycles and taking care of other hygienic practices during their periods. People were also motivated to spread awareness in their nearby developing villages and other rural areas and encouraging people to use proper toilets during disposal of their wastes. A well supportive behavior was shown by the community indicating the interest of community in amending their lifestyles by practicing appropriate hygienic practices.